Peningkatan Kerapatan Kayu Samama Melalui Pre-kompresi Asam Sitrat (Density Improvement of Samama Wood by Pre-compression of Citric Acid) - Azis Rumbaremata; Tekat D Cahyono; Teguh Darmawan; Sukma S Kusumah; Fazhar Akbar; Wahyu Dwianto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2019)
Samama wood (Anthocephalus macrophyllus (Roxb.) Havil.) is a potential fast-growing species of Sulawesi and Maluku. This study aimed to increase the density of the wood through citric acid pre-compression. The temperature/time pressing formula and the optimal concentration of citric acid for fixation were also determined. Water saturated samples of (5x5x4) cm3 (L = longitudinal x T = tangential x R = radial) were pre-compressed at 100 °C for one hour to reach drying set. Subsquently, the samples were soaked for 4 hours in a citric acid solution of 5% and 10% concentration, drained and wrapped in aluminum foil before re-pressed at 180 °C for 10, 20, 30, 40, 50, and 60 minutes. Fixation was measured by soaking the samples into water for 24 hours at room temperature. The results showed that the moisture contents at fiber saturation point ranged from 33.15-33.94%, with density of 0.46 g cm-3 and oven dry density of 0.37 g cm-3. The L, T, and R shrinkages were 0.18-0.20%, 4.13-4.14%, and 2.53-3.10%, respectively; while the T/R ratio was 1.33-1.63%. Pre-compression can only be done at a compression target of 25% with compression level of 19.57-20.01%. Pre-compression increased the oven dry density of 17.11-20.13% to 0.44-0.45 g cm-3. After thickness recovery, the weight of the oven dried samples increased by 1.79-2.72% at the 5% citric acid concentration and by 12.04-15.25% at the 10% citric acid concentration.  Permanent fixation achieved at 180 °C for 50 minutes pressing time with 10% citric acid concentration.